1992
DOI: 10.2534/jjasnaoe1968.1992.493
|View full text |Cite
|
Sign up to set email alerts
|

Local Approach to Notch Depth Dependence of CTOD Results

Abstract: SummaryThe effect of the notch depth on the critical CTOD value at cleavage fracture initiation was analysed by the local approach. Three-point bend CTOD specimens with different notch depth extracted from a high strength steel were tested at the lower shelf temperature. The critical CTOD values showed large dependence on the notch depth. Three-dimensional elastic-plastic finite element analyses were performed to investigate the crack tip stress fields for all specimen geometries. The numerical results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The probability of specimen fracture, specimen P , can be calculated as a function of δ , assuming values for { } It is worth mentioning that, the statistical distribution of critical CTOD can be written as Equation 7, including CTOD parameters m δ and b δ , which was also used in the studies of Ruggieri et al 4 .…”
Section: Local Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability of specimen fracture, specimen P , can be calculated as a function of δ , assuming values for { } It is worth mentioning that, the statistical distribution of critical CTOD can be written as Equation 7, including CTOD parameters m δ and b δ , which was also used in the studies of Ruggieri et al 4 .…”
Section: Local Approachmentioning
confidence: 99%
“…The toughness scatter studies in mechanical failure were introduced by the weakest link probabilistic theory to obtain the material fracture toughness. Based on this methodology, Ruggieri et al 4 , Tagawa et al 5 , and Kawata et al 6 investigated the fracture toughness distribution obtained from the CTOD test. In Lin et al 7 , predictions for the fracture toughness are shown, taking into account the microstructure and temperature, using a quantitative weakest-link model.…”
Section: Introductionmentioning
confidence: 99%
“…stress. An effective stress 8,9) considering a random spatial distribution of microcracks was employed as σ eff in Eq. (2).…”
Section: Strength Mismatch Effect On Toughness Valuesmentioning
confidence: 99%
“…It has been widely demonstrated the Weibull stress at brittle fracture initiation could be material constant. [7][8][9][10] Therefore, this Weibull stress criterion enables transferability analysis; effect of specimen geometry and size as well as loading mode on brittle fracture load can be predicted. With focusing on this local approach, a development of a new estimation method of hydrogen-induced unstable fracture in brittle manner has been advanced taking the deterioration of materials due to hydrogen into consideration.…”
Section: Introductionmentioning
confidence: 99%